(untitled) (Research, Society and Development, 2021)
Introduction: Skin changes and skin cancer resulting from sun exposure represent a global health problem, and its control, prevention and promotion are the responsibility of the Public Health sector and everyone. Protection from light is essential as sun damage is cumulative and can increase the risk of skin cancer and skin disorders. Although exposure to sunlight has beneficial effects, such as symptoms of well-being, production. Objective: To analyze the protection effectiveness of the use of photoprotectors in truck drivers, listing the diseases triggered by sun exposure in these professionals. Method: Descriptive research of qualitative nature and bibliographical review. Results: The investigation showed that many of the truck drivers do not use sunscreens, which exposes them to the risk of developing skin diseases such as skin cancer. Conclusion: There is a need to sensitize truck drivers about the importance of using sunscreens.